Responsibility - Darling-Smith, Barbara, 1954- (Lanham, MD Lexington, 2007)
Contents : Pt 1 : Responsibility and selfhood : Responsible fictions -- Responsibility without a self -- "The way is made in the walking": responsiblity as a relational virtuosity -- "Where art thou?": biblical perspectives on responsibility. Pt 2 : Responsible roles towards other human beings : Moral responsibility in a democratic society -- Am I my brother's keeper?: an Aristotelian take on responsibilty for others -- Tasteless historical stories: a historical theologian's responsibility to past and present -- Balancing medicine's moral ledger: realigning trust and responsiblity -- Responsibilities of corporations: managing profitably and morally. Pt 3 : Responsibility towards nonhuman beings and the Earth : Toward an art of dwelling -- Ecological and social responsibility: the making of the Earth charter. Appendix : The Earth charter. Includes bibliographical references and index.
Keywords: Responsibility